ANALISIS KECURANGAN DALAM TAKARAN DAN TIMBANGAN OLEH PEDAGANG DITINJAU DARI FIQIH RIBA (STUDI KASUS DI PASAR BANDAR KEDIRI) - Linda Khoirun Nisak, dkk (Qawanin: Jurnal of Economic Syaria Law, 2017)
n marketing activities, there are elements called the marketing mix that includesÂ product, price and promotion, and one of the elements that were also veryÂ instrumental is a place in this case a distribution channel.In an effort to increaseÂ sales of its products, the company has a strategy that is by giving gifts toÂ customers with certain conditions. Gift-giving is done by a distributor. Being a distributor must have the ability to sell a product. Not only a limited ability alone,Â ethics must be owned by a distributor.Based on research through interviews,distributor of coffee products Tora Bika has adopted the ethics promotion. EthicsÂ used has been well received by consumers with evidence that many new customersÂ who take the program prizes that have been awarded by the company. So ToraÂ Bika Coffee product sales increased.From the description above, the company isÂ expected to add strategies such as gift order coffee products Tora Bika could beÂ easily bought among consumers. Kata Kunci: etika distributor, pemberian hadiah, daya beli